2019
DOI: 10.4314/ijbcs.v13i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Analyse socioéconomique du système de commercialisation de la banane plantain dans la région de l’Ouest Cameroun

Abstract: La commercialisation de la banane-plantain occupe une place prépondérante dans les flux des produits agricoles. Cette étude met en exergue le fonctionnement des différents systèmes de commercialisation du produit et leurs rentabilités économiques dans la région de l'Ouest Cameroun. Des enquêtes ont été menées auprès de 167 acteurs de la filière (33 producteurs, 50 collecteurs, 25 grossistes, 44 détaillants et 15 transporteurs) dans la région. Les résultats montrent que les catégories d'acteurs impliquées dans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The key determinants that can increase household food diversity and improve to crisis period were the humanitarian's response to assure their food security for local populations in the Bankass and Koro Circles. However, small families were observed to be more food secure than medium and large families, indicating that size and food security are negatively related Kennedy et al (2010); Fouepe et al (2019), he found that same comments.…”
Section: Discussionmentioning
confidence: 81%
“…The key determinants that can increase household food diversity and improve to crisis period were the humanitarian's response to assure their food security for local populations in the Bankass and Koro Circles. However, small families were observed to be more food secure than medium and large families, indicating that size and food security are negatively related Kennedy et al (2010); Fouepe et al (2019), he found that same comments.…”
Section: Discussionmentioning
confidence: 81%